2013
DOI: 10.1007/s10452-013-9458-8
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the roles of spatial and environmental variables in shaping benthic algal assemblages in rivers of central and northern China

Abstract: Benthic algae were collected from central and northern Chinese rivers to test the hypothesis that geographic location has significant contributions in shaping algal assemblages. We used Moran's eigenvector maps (MEM) to model spatial components and variation partitioning to quantify the influences of spatial and environmental variables on regional patterns of algal richness and community composition, respectively. We found that variation in algal richness was attributed to MEM component 2, 8, and 9 and the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…4). This was in accordance with Abbreviations of environmental variables as in Table 2 Hydrobiologia (2014) 732:49-60 55 Passy (2007) and Tang et al (2013), but not consistent with Potapova & Charles (2002), Urrea & Sabater (2009), Smucker & Vis (2011 and Göthe et al (2013). For example, Passy (2007) found that the unique contribution of spatial dataset (16%) to the explained diatom variance was higher than that of environmental variables (9%).…”
Section: Diatom-environmental Relationships Across a Large Spatial Scalesupporting
confidence: 74%
See 3 more Smart Citations
“…4). This was in accordance with Abbreviations of environmental variables as in Table 2 Hydrobiologia (2014) 732:49-60 55 Passy (2007) and Tang et al (2013), but not consistent with Potapova & Charles (2002), Urrea & Sabater (2009), Smucker & Vis (2011 and Göthe et al (2013). For example, Passy (2007) found that the unique contribution of spatial dataset (16%) to the explained diatom variance was higher than that of environmental variables (9%).…”
Section: Diatom-environmental Relationships Across a Large Spatial Scalesupporting
confidence: 74%
“…For example, Passy (2007) found that the unique contribution of spatial dataset (16%) to the explained diatom variance was higher than that of environmental variables (9%). Tang et al (2013) observed that spatial proportions were higher than that of environmental variables among the total explained variance in both algal metrics. However, Urrea & Sabater (2009) got a less influence of spatial factors (6.1%) than physicalchemistry variables (11.3%) on diatom community.…”
Section: Diatom-environmental Relationships Across a Large Spatial Scalementioning
confidence: 90%
See 2 more Smart Citations
“…Ten PCNM variables were obtained in the case of our study. Redundancy analysis (RDA) was then applied to detect relationships between algal relative abundance and PCNM variables (RDA-PCNM) (Borcard et al, 2011), accompanied by forward selection procedures for selecting important PCNM variables (Blanchet et al, 2008;Tang et al, 2013b). RDA was re-run with selected PCNM variables, and significant RDA axes were identified by the Monte Carlo permutation test (with 9,999 times).…”
Section: Statistical Analysesmentioning
confidence: 99%